STRATEGI PENYULUHAN AGAMA HINDU MELALUI PROGRAM SIARAN DI STASIUN TELEVISI BALI TV - Kadek Ria Parwati; Gede Agus Jaya Negara; I Kadek Edi Palguna (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2023)
Hindu religious counseling is a method of explaining the Hindu religion which aims to foster Hindu religious people. In everyday life, people still need guidance related to the teachings of Hinduism to be used as a way of life in order to achieve life goals. In the current era of digitalization, religious counseling has been packaged through mass media such as television. This is done by the television station BALI TV to provide education on Hinduism through constructive and educational broadcasts and impart knowledge to the wider community. The problems in this research are: (1) What are the broadcast programs on BALI TV that are used as a medium for teaching Hinduism? (2) What is the strategy of BALI TV in providing counseling on Hinduism? (3) What are the implications of the Hindu religious counseling program broadcast by BALI TV? To answer these problems, this study used a qualitative research method with a descriptive approach system. The theory used is Informative Theory and TheoryUses and Effects. The results of this study indicate (1) The broadcast program owned by BALI TV in providing counseling on Hinduism is the Dharma Wacana broadcast program and the Istadewata broadcast program (2) The strategy carried out by BALI TV in providing Hindu religious counseling is very good by considering the community's need to consume interesting program. (3) The implications of the existence of broadcast programs related to Hindu religious education are positive and constructive and are felt by various parties, both for the BALI TV television station and the community from various groups.